تفعيل مستوى معالجة المعلومات لمواد القانون الدولي في كرة اليد على نسب الأخطاء القانونية في المباريات التعليمية " لطالبات كلية التربية الرياضية بالإسكندرية " - سالم، دعاء الدرديري أبو الحسن (جامعة الزقازيق - كلية التربية الرياضية للبنات, 2009)
استهدفت هذه الدراسة تفعيل مستوى معالجة المعلومات لمواد القانون الدولي في كرة اليد من خلال تصميم كتيب مبرمج لإكساب الطالبات المعلومات المتعلقة بالقانون، وتصميم اختبار معرفي، بناء استمارة لتقييم وملاحظة نسب الأخطاء والعقوبات القانونية في المباريات التعليمية. \ وقد اشتملت عينة الدراسة على (56) طالبة من طالبات الفرقة الثالثة (شعبة تعليم) بكلية التربية الرياضية بالإسكندرية، وقد تم اختيارهن بالطريقة العمدية، وتم تطبيق الدارسة الأساسية في الفترة من (1/ 3/ 2010- 8/ 5/ 2010) في الفصل الدراسي الثاني من العام الجامعي 2009/ 2010. \ تم جمع البيانات باستخدام اختبار التحصيل المعرفي، استمارة تقييم وملاحظة الأخطاء والعقوبات القانونية عن طريق القياس القبلي والبعدي لمجموعتين إحداهما تجريبية والأخرى ضابطة ومقارنة نتائجهم وإيجاد العلاقة بين درجة التحصيل المعرفي ونسب الأخطاء القانونية. \ وقد أمكن التوصل إلى أن الكتيب المبرمج له تأثير إيجابي على مستوى معالجة المعلومات لمواد القانون الدولي لكرة اليد، وكذلك على تحسن نسب الأخطاء القانونية والعقوبات في المباريات التعليمية، وفي ضوء الاستنتاجات السابقة توصي الباحثة باستخدام الكتيب المبرمج لتدريس قانون كرة اليد، استخدام اختبار التحصيل المعرفي لتقيم مستوى معالجة المعلومات المرتبطة بالقانون، الاهتمام باستخدام الاستمارة قيد البحث في تقييم وملاحظة الأخطاء القانونية والعقوبات في المباريات التعليمية لطالبات كلية التربية الرياضية بالإسكندرية. The study aims to activate to Data Processing Level of International Rules in Handball by designing a programmed booklet to acquire students’ information related to rules, design a cognitive test, institute an application to evaluate and note the legal mistakes in the educational contests. \ The sample included (56) female students from the third year (Education branch) in the Faculty of Physical Education for Girls in Alexandria, they were tested deliberately, the major study was applied in the period of (7/3/2010 to 8/5/2010) in the second Term\ of the academic year (2009/2010). \ The data collection was carried out with using the cognitive study test, and the application of evaluation and noting of the legal mistakes by the pre-post measurements for the two groups - a control one and an experimental one and compare their results , finding the relationship between the cognitive study degree and the legal mistakes rates, the researcher fouid that the programmed booklet has a positive effect on Data Processing Level of International Rules in Handball, and improved the legal mistakes rates and punishments in the educational contests. \ In the high light of the previous results, the researcher recommends to use the programmed booklet to teach the handball rules, utilizing the cognitive study test to evaluate Data Processing Level related to rules, give attention to utilize the application under discussion to evaluate and note the legal mistakes and punishments in the educational contests with the female students of the faculty of physical education for girls in Alexandria.
Keywords: طالبات كليات التربية الرياضية -- القانون الدولي الرياضي -- كرة اليد -- القوانين والتشريعات -- الأخطاء القانونية -- المباريات التعليمية -- الإسكندرية -- التمارين الرياضية -- المهارات الرياضية -- معالجة المعلومات